COOPERATION BETWEEN THE MINISTRY OF NATIONAL EDUCATION AND LOCAL SELF-GOVERNMENT BODIES OF THE PERM PROVINCE DURING THE PERIOD “PREPARATORY WORK FOR THE COMPULSORY EDUCATION INTRODUCTION” - S. V. Golikova (Образование и наука)
Introduction. In the history of education, there is still considerable shortfall of the question on mechanisms realization of the general literacy idea in Russia in the beginning of the last century, which gained its popularity around the world at the turn of the 19–20th centuries. Meanwhile, the stage of preparation for cosmopolitan diffusion of compulsory primary education in the Russian Empire, marked by emergence of the special bill drafted by the Ministry of National Education in 1907, is of great interest to the research of opportunities of interaction of the state institutes and regional local self-government bodies (Zemstvo in the Russian language).The aim of the publication is to show the efficiency of joint activities of local self-government bodies and national administrative bodies with reference to example of the system of primary national education formation during 1908–1913 in the Perm province.Methodology and research methods. The methodological base of the present research is based on: the “center-periphery” conceptual model; methods of the retrospective chronological analysis, synthesis, generalization and interpretation of archival documents.Results and scientific novelty. The methodological perspective of studying the history of primary schools organization in pre-revolutionary Russia is proved. The choice of regional (provincial) scale of this process enables to consider features of the public educational policy at the subcountry level; the center-periphery approach to the discussed subject makes it possible to understand more deeply the essence and purposes of the major educational reform. The assessment of the contents on the introduction of compulsory primary education in the Russian Empire is given; the draft bill established standards, new to educational practice, can be listed as follows: “normal duration of training”, “normal school age”, “normal number of children”, “normal school area” (“normal school radius”) and “normal school kit”. The key value and importance of the document consisted in differentiation of powers: in contrast to the Ministry of National Education, the structures of territorial and municipal government bodies had greater freedom of action and were assigned a leading part to put the idea of a compulsory education (Vseobuch in the Russian language) into reality.Dynamics of statistical data on financial government aid to national education is analysed. Activities of all-imperial and provincial school building funds are characterized. It is proved that the essential growth of public financial recourses against the background of vigorous territorial activity not only led to rapid increase in number of schools, but also turned them from local-regional into ministerial-local ones. The conclusion is drawn that due to close cooperation of the Ministry of National Education with local government bodies, the period 1907– 1913 was a key stage of an institutionalization of the Russian compulsory education during the pre-revolutionary times.Practical significance. The results of the research can be adopted when preparing academic courses on the History and Sociology of Education, as well as the Economics of Knowledge.